CHLORITIZATION OF LATE ORDOVICIAN K-BENTONITES FROM THE NORTHERN BALTIC PALAEOBASIN-INFLUENCE FROM SOURCE MATERIAL OR DIAGENETIC ENVIRONMENT? - Hints R.; Kirsimäe K.; Somelar P.; Kallaste T.; Kiipli T. (My University, 2006)
The Baltic Ordovician-Silurian sedimentary succession embodies numerous altered volcanic ash beds that are illite-smectite dominated. Only a few beds rich in chlorite-smectite are known from the Upper Ordovician Pirgu Stage of Estonia. Mixed-layer chlorite-smectite occurs commonly in low-grade metamorphic and hydrothermal environments. However, chloritic K-bentonites of the Pirgu Stage have never been buried deeply and lack signs of metamorphic overprinting. In order to understand the origin of chloritization, three distinct beds were sampled in 14 drillcores from Estonia and Latvia and analysed by means of XRD and SEM. The principal authigenic assemblage of the bulk samples consists of chlorite-smectite (corrensite) together with illite-smectite and K-feldspar. The actual mineral composition of K-bentonites though varies from sample to sample. The clay mineral assemblages range from virtually pure chlorite-smectite to illite-smectite dominated assemblages with minor or no chlorite-smectite. The proportion of chlorite-smectite in K-bentonites shows systematic lateral variations: the share of chloritic phases is highest in the shallower-water part of the palaeobasin and decreases towards the deeper part of the basin. Such regular lateral variations suggest a possible link between chloritization and the configuration of ancient palaeobasin. The present study suggests that the chloritization of primary felsic ashes occurred during early diagenesis and that it was caused by an influx of Mg-rich water probably from a marine sabkha-type environment. © 2006 Elsevier B.V. All rights reserved.
Keywords: BALTIC PALAEOBASIN; CHLORITE-SMECTITE; DIAGENESIS; K-BENTONITE; PALEOZOIC; PIRGU; Paleozoic::Ordovician; Палеозой::Ордовикская; Paleozoic::Silurian; Палеозой::Силурийская